2017
DOI: 10.4103/1735-3327.218562
|View full text |Cite
|
Sign up to set email alerts
|

Masking ability of a zirconia ceramic on composite resin substrate shades

Abstract: Background:Masking ability of a restorative material plays an important role to cover discolored tooth structure; however, this ability has not yet been well understood in zirconia-based restorations. This study assessed the masking ability of a zirconia ceramic on composite resin substrates with different shades.Materials and Methods:Ten zirconia disc specimens, with 0.5 mm thickness and 10 mm diameter, were fabricated by a computer-aided design/computer-aided manufacturing system. A white substrate (control)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 29 publications
1
11
0
1
Order By: Relevance
“…Moreover, Jirajariyavej et al suggested the use of yellow‐shaded zirconia abutments along with increasing the thickness of the ceramic restoration to produce a more‐esthetic color. To compensate for the background aspect, several solutions are proposed: using backgrounds with the color close to the target color, masking backgrounds with proper cements, and increasing the zirconia thickness …”
Section: Clinical Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Jirajariyavej et al suggested the use of yellow‐shaded zirconia abutments along with increasing the thickness of the ceramic restoration to produce a more‐esthetic color. To compensate for the background aspect, several solutions are proposed: using backgrounds with the color close to the target color, masking backgrounds with proper cements, and increasing the zirconia thickness …”
Section: Clinical Factorsmentioning
confidence: 99%
“…To achieve optimum esthetics for monolithic zirconia restorations in patients needing a composite resin foundation, the corresponding restoration shade should be chosen for the foundation . When a custom post and core is the option, the use of a non‐precious gold‐colored alloy or a zirconia ceramic is recommended rather than a nickel‐chromium alloy .…”
Section: Clinical Factorsmentioning
confidence: 99%
“…A well‐documented spectrophotometer (SpectroShade Micro; MHT Optic Research AG, Verona, Italy) was used for all color measurements. A silicone putty (Speedex; Coltene, Altstatten, Switzerland) was molded to the mouthpiece of the spectrophotometer to match the conditions for all specimens, to provide a seat for the backgrounds, and to avoid external light . Each veneered zirconia specimen was assigned to a background specimen, and color measurements were conducted before cementation (zirconia specimens were properly placed on backgrounds without an intermediate) and after cementation.…”
Section: Methodsmentioning
confidence: 99%
“…Considering the thickness and translucency of both compartments, light transmission through these restorations can be anticipated . Therefore, underlying structures such as dental backgrounds and cements may affect the color of zirconia‐based restorations …”
mentioning
confidence: 99%
“…In clinical restorations, the recommended range of thickness for monolithic zirconia is 0.5 – 2.0 mm 13. It has also been found that 0.5-mm low-translucency zirconia ceramic could not mask tooth discoloration 14. An increase in thickness improves the masking ability of translucent zirconia 15.…”
Section: Introductionmentioning
confidence: 99%